Evaluating the use of nitrogen and phosphorous fertilization as crop management options for maize adaptation to climate change in the Nigeria savannas - Tofa, A.; Kamara, A.; Babaji, B.A.; Adnan, A.A.; Ademulegun, T.; Bebeley, J.F. (IOP Publishing, 2023)
Poor soil fertility and climate variability are major constraints to maize production in the Nigeria savannas. The application of nitrogen (N) and phosphorus (P) as adaptation strategy may enhance maize yield under climate change. In this study, the already calibrated and validated CERES-maize model in DSSAT was used to simulate the response of maize varieties to N and P in three agroecological zones. Similarly, the model, coupled with data for representative concentration pathways (RCP4.5 and RCP8.5) scenarios, was applied to simulate maize yields for mid-century and end-of-century periods and to estimate the effect of use of N and P as a strategy for maize adaptation to climate change. Results of a 30-year sensitivity analysis showed that the optimum grain yields were obtained with application of 150 kg N + 30 kg P ha–1 to the two varieties in Kano and Zaria. In Abuja, the optimum grain yields were obtained with the application of 150 kg N ha–1 + 30 kg P ha–1 to SAMMAZ–15 and 120 kg N ha–1 + 30 kg P ha–1 to SAMMAZ–16. When P is not applied, the simulation results show that across all N rates, maize yield would decrease by 25%–52% and 32%–52% for the mid- and end-of-century, respectively, under RCP4.5 for both varieties. There would be a greater reduction under RCP8.5, with a decrease of 32%–59% and 52%–69% under mid- and end-of-century scenarios, respectively. When P is applied at 30 kg ha−1, the reduction in yield due to climate change is lower. Under RCP4.5, the yield would decrease by 9%–15% and 11%–21% for the mid- and end-of-century, respectively. There would be a reduction of 12%–21% and 32%–41% for mid-century and end-of-century, respectively, under RCP8.5 scenario. This suggests that the application of optimum P could reduce the impact of yield loss due to climate change.